BCG vaccination induces enhanced frequencies of memory T cells and altered plasma levels of common γc cytokines in elderly individuals - Nathella Pavan Kumar (Public Library of Science (PLoS), 2021)
BCG vaccination is known to induce innate immune memory, which confers protection against heterologous infections. However, the effect of BCG vaccination on the conventional adaptive immune cells subsets is not well characterized. We investigated the impact of BCG vaccination on the frequencies of T cell subsets and common gamma c (γc) cytokines in a group of healthy elderly individuals (age 60–80 years) at one month post vaccination as part of our clinical study to examine the effect of BCG on COVID-19. Our results demonstrate that BCG vaccination induced enhanced frequencies of central (p<0.0001) and effector memory (p<0.0001) CD4+ T cells and diminished frequencies of naïve (p<0.0001), transitional memory (p<0.0001), stem cell memory (p = 0.0001) CD4+ T cells and regulatory T cells. In addition, BCG vaccination induced enhanced frequencies of central (p = 0.0008), effector (p<0.0001) and terminal effector memory (p<0.0001) CD8+ T cells and diminished frequencies of naïve (p<0.0001), transitional memory (p<0.0001) and stem cell memory (p = 0.0034) CD8+T cells. BCG vaccination also induced enhanced plasma levels of IL-7 (p<0.0001) and IL-15 (p = 0.0020) but diminished levels of IL-2 (p = 0.0033) and IL-21 (p = 0.0020). Thus, BCG vaccination was associated with enhanced memory T cell subsets as well as memory enhancing γc cytokines in elderly individuals, suggesting its ability to induce non-specific adaptive immune responses.